A Large-Scale Comparative Metagenomic Study Reveals the Functional Interactions in Six Bloom-Forming Microcystis-Epibiont Communities - Li, Qi; Lin, Feibi; Yang, Chen; Wang, Juanping; Lin, Yan; Shen, Mengyuan; Park, Min S.; Li, Tao; Zhao, Jindong (Frontiers in Microbiology, 2018)
Cyanobacterial blooms are worldwide issues of societal concern and scientific interest. Lake Taihu and Lake Dianchi, two of the largest lakes in China, have been suffering from annual Microcystis-based blooms over the past two decades. These two eutrophic lakes differ in both nutrient load and environmental parameters, where Microcystis microbiota consisting of different Microcystis morphospecies and associated bacteria (epibionts) have dominated. We conducted a comprehensive metagenomic study that analyzed species diversity, community structure, functional components, metabolic pathways and networks to investigate functional interactions among the members of six Microcystis-epibiont communities in these two lakes. Our integrated metagenomic pipeline consisted of efficient assembly, binning, annotation, and quality assurance methods that ensured high-quality genome reconstruction. This study provides a total of 68 reconstructed genomes including six complete Microcystis genomes and 28 high quality bacterial genomes of epibionts belonging to 14 distinct taxa. This metagenomic dataset constitutes the largest reference genome catalog available for genome-centric studies of the Microcystis microbiome. Epibiont community composition appears to be dynamic rather than fixed, and the functional profiles of communities were related to the environment of origin. This study demonstrates mutualistic interactions between Microcystis and epibionts at genetic and metabolic levels. Metabolic pathway reconstruction provided evidence for functional complementation in nitrogen and sulfur cycles, fatty acid catabolism, vitamin synthesis, and aromatic compound degradation among community members. Thus, bacterial social interactions within Microcystis-epibiont communities not only shape species composition, but also stabilize the communities’ functional profiles. These interactions appear to play an important role in environmental adaptation of Microcystis colonies.